Efficient Transition Metal-Catalyzed Reactions of Carboxylic Acid Derivatives with Hydrosilanes and Hydrosiloxanes, Afforded by Catalyst Design and the Proximity Effect of Two Si–H Groups - Nagashima, Hideo (Synlett, 2015)
The discovery of the ruthenium cluster μ3,-(η2:η3:η5-acenaphythylene)Ru3(CO)7 (1), which is active in catalytic reactions involving Si–H bond activation, and the rate enhancement by the proximity effect of two Si–H groups enabled the reduction of carboxylic acid derivatives with hydrosilanes under mild reaction conditions. A judicious choice of the hydrosilane and of the additives led to a remarkably selective reduction. Besides simple reduction, the treatment of carboxylic acid derivatives with hydrosilanes in the presence of 1 led to new reactions involving several C–O and C–C bond-forming as well as C–O bond-cleavage steps. These reactions included polymerization, rearrangement, and aromatic substitution. The use of inexpensive 1,1,3,3-tetramethyldisiloxane (TMDS) facilitated the efficient reduction of amides to amines using either 1, commercially available platinum compounds, or environmentally friendly iron complexes. The conversion of tertiary amides into aldenamines was achieved by iridium catalysis. In the ruthenium-, iridium-, platinum-, and iron-catalyzed reduction of amides, the use of the reducing reagent polymethylhydrosiloxane (PMHS) resulted in self-encapsulation of the residual metal species into the formed silicone gel to give the ‘metal-free’ product in a straightforward way.1 Introduction2 Two Key Preliminary Investigations2.1 A Ruthenium Cluster for Si–H Bond Activation2.2 Proximity Effect of Two Si–H Groups for Rate Enhancement3 Ruthenium-Catalyzed Reduction of Carboxylic Acid Derivatives3.1 From Ketones to Less Reactive Carboxylic Acid Derivatives3.2 Self-Encapsulation of the Residual Metals into Silicone Gel4 Extension to C–O and C–C Bond-Forming Reactions4.1 Reduction versus Ring-Opening Polymerization of Cyclic Ethers4.2 Polymerization versus Rearrangement of Vinyl Ethers4.3 Is ‘R3Si+’ Involved in the Reactions?4.4 Applications of ‘R3Si+’-Mediated Reactions5 Reductions with Unique Selectivity6 Surfing the Periodic Table7 Concluding Remarks
Keywords: homogeneous catalysis, reduction, hydrosilylation, amides, carboxylic acids, esters, metal complexes